Correlated Electrical Conductivities to Chemical Configurations of Nitrogenated Nanocrystalline Diamond Films - Abdelrahman Zkria; Hiroki Gima; Eslam Abubakr; Ashraf Mahmoud; Ariful Haque; Tsuyoshi Yoshitake (Nanomaterials, 2022)
Diamond is one of the fascinating films appropriate for optoelectronic applications due to its wide bandgap (5.45 eV), high thermal conductivity (3320 W m−1·K−1), and strong chemical stability. In this report, we synthesized a type of diamond film called nanocrystalline diamond (NCD) by employing a physical vapor deposition method. The synthesis process was performed in different ratios of nitrogen and hydrogen mixed gas atmospheres to form nitrogen-doped (n-type) NCD films. A high-resolution scanning electron microscope confirmed the nature of the deposited films to contain diamond nanograins embedded into the amorphous carbon matrix. Sensitive spectroscopic investigations, including X-ray photoemission (XPS) and near-edge X-ray absorption fine structure (NEXAFS), were performed using a synchrotron beam. XPS spectra indicated that the nitrogen content in the film increased with the inflow ratio of nitrogen and hydrogen gas (IN/H). NEXAFS spectra revealed that the σ*C–C peak weakened, accompanied by a π*C=N peak strengthened with nitrogen doping. This structural modification after nitrogen doping was found to generate unpaired electrons with the formation of C–N and C=N bonding in grain boundaries (GBs). The measured electrical conductivity increased with nitrogen content, which confirms the suggestion of structural investigations that nitrogen-doping generated free electrons at the GBs of the NCD films.